Cost-effectiveness of non-vitamin K antagonist oral anticoagulants for stroke prevention in non-valvular atrial fibrillation: a systematic and qualitative review. (3rd March 2016) - Liberato, Nicola Lucio; Marchetti, Monia
Abstract: The introduction of non-vitamin K antagonist oral anticoagulants (NOACs) into clinical practice represented a major change in the treatment of non-valvular atrial fibrillation (NVAF); drugs as effective as the gold standard were available, rapidly functioning and without major interferences with drugs and foods. However, a huge increase in the economic burden of NVAF was predicted, and many cost-effectiveness analyses were developed to aid policy makers and clinicians in implementing strategies for the prevention of stroke in NVAF. The present systematic review identified 54 studies from 21 different countries, reporting the incremental cost-effectiveness of dabigatran, apixaban, rivaroxaban and edoxaban. A critical appraisal of the studies was conducted in order to highlight consolidated results and biases.